Fundamental studies of magneto-optical borogermanate glasses and derived optical fibers containing Tb3+ - Franco, Douglas F. [UNESP]; Fernandes, Roger G. [UNESP]; Felix, Jorlandio F.; Mastelaro, Valmor R.; Eckert, Hellmut; Afonso, Conrado R.M.; Messaddeq, Younès [UNESP]; Messaddeq, Sandra H.; Morency, Steeve; Nalin, Marcelo [UNESP] (Elsevier, 2021)
New magnetic glass compositions, based on system (100-x) (60GeO2 -25B2O3 -4Al2O3 -10Na2O-1PbO) - xTb4O7 were prepared by the melt-quenching technique. The materials were systematically characterized with respect to their structural (XRD, EXAFS, XANES and Raman), thermal (DSC), morphological, optical, magnetic and magneto-optical (MO) properties. Morphological and magnetic measurements show the homogeneous distribution of the Tb3+ ions as the magnetic susceptibility increases proportionally to the rare earth content. The optical window covers the range from 0.5 up to 1.6 μm, limited by absorption due to 4f8 -> 4f7 5 d 1and 4f8 -> 4f8 transitions of Tb3+. XANES and EXAFS measurements at the Ge-K edge show that the germanium atoms are always tetrahedrally coordinated, while results at the Tb-LIII edge shows terbium atoms to be eight-coordinated and exclusively present in the oxidation state 3+ independently of the glass composition. MO measurements show that the Verdet constant (VB) increases linearly with the Tb3+ concentration reaching the value of -83.9 rad T-1m-1 at 650 nm for glass containing 8 mol% of Tb4O7. Good thermal stability (ΔT = 200 °C) allowed obtaining an optical fiber of a glass containing 4 mol% of Tb4O7 featuring VB values of -37.9, -23.6 and -5.89 rad T-1 m-1, at 500, 650 and 1550 nm, respectively.
Keywords: Faraday rotation; Magneto-optical glasses; Optical fibers; Verdet constant